KEDUDUKAN HUKUM KARYAWAN BANK PASCA DILAKUKAN MERGER, KONSOLIDASI DAN AKUISISI - Misranto Misranto (Institute for Research and Community Services (LPPM) of Wijaya Kusuma Surabaya University, 2007)
One of the terms of economic crisis in Indonesia is monetary crisis. Monetary crisis or economic up to now still occur in Indonesia, which is noted by banks which undergo liquidity that causes the banks “willing or not, wanting or not” have to throw away its stirring and shake hands with the other banks to build cooperation or to look for strategic partner in order to survive by doing merger consolidation, and bank acquisition. However, the member of merger banks should notice the effects of law appeared due to merger consolidating, and that acquisition, in addition to its bank employees, because the employees have the full control as the bank operational. Bank is impossible having its activity well without full supports of its employees.